Reparative action of hydrogel polygexamethylenuanidine hydrochloride - S. N. Lebedeva; O. S. Ochirov; S. A. Stelmakh; M. N. Grigor’eva; S. D. Zhamsaranova; D. M. Mognonov (Бюллетень сибирской медицины, 2018)
Polyguanidines are characterized by pronounced antimicrobial activity and are widely used as the main active substance of disinfectants. Polymers of this class possess the property of gel formation, which, together with biological activity, opens the prospect of obtaining an effective single-component agent or basis for an external preparation for the therapy of skin lesions. Earlier, we developed a method for the production of a hydrogel based on polyhexamethyleneguanidine hydrochloride, which involves the cross-linking of the terminal amino groups of the branched polymer with formaldehyde.The purpose of the study was to observe the effect of hydrogel polyhexamethyleneguanidine hydrochloride on the progression of wound healing.Materials and methods. An experiment on the evaluation of the wound healing action of hydrogel was carried out under conditions simulating a linear cutaneous wound, a muscular wound, and a thermal burn. The comparative drug was the pharmacopoeian drug Levomecol.Results. It has been established that hydrogel has a pronounced wound healing effect, as evidenced by the results of ruminant thoracic anatomy and pathomorphology of the sections, which shows accelerated ripening of granulation tissue and scar formation. By the method of vulnografiya it was shown that the daily decrease in wound area is most pronounced in the hydrogel group, which also indicates a pronounced reparative effect. It was determined that the hydrogel activates the growth of antioxidatic activity and leukocytes in the blood of animals in dynamics on the 10th, 17th and 24th day of the experiment, amounting to 56, 34 and 21%, and of leukocytes – 32, 30, 10% in relation to the intact animals.Conclusion. Thus, on the model of a linear cutaneous wound, a muscular wound, and a thermal burn, the healing effect of the hydrogel PGMGh/f is established, as evidenced by the results of the early exercise, vulnografiya and pathomorphological studies. It is noted that the hydrogel PGMG h/f has an effect on the content of antioxidants and leukocytes in the blood, contributing to the normalization of their quantity.